2007
DOI: 10.1037/1541-1559.4.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Designing websites for persons with cognitive deficits: Design and usability of a psychoeducational intervention for persons with severe mental illness.

Abstract: The purpose of this study was to develop an understanding of the design elements that influence the ability of persons with severe mental illness (SMI) and cognitive deficits to use a website, and to use this knowledge to design a web-based telehealth application to deliver a psychoeducation program to persons with schizophrenia and their families. Usability testing was conducted with 98 persons with SMI. First, individual website design elements were tested. Based on these results, theoretical website design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 43 publications
8
137
0
2
Order By: Relevance
“…Third, although a number of studies provided details on the procedures employed to develop the interventions, only four intervention studies reported involving end-users at some point in the design process (Rotondi et al, 2007(Rotondi et al, , 2010Anttila et al, 2012;Granholm et al, 2012;Alvarez-Jimenez et al, 2013). These findings are at odds with general calls to involve patients in all stages of the design process in order to develop engaging, meaningful and clinically relevant interventions (Hagen et al, 2012).…”
Section: Methodological Issues and Future Researchmentioning
confidence: 44%
“…Third, although a number of studies provided details on the procedures employed to develop the interventions, only four intervention studies reported involving end-users at some point in the design process (Rotondi et al, 2007(Rotondi et al, , 2010Anttila et al, 2012;Granholm et al, 2012;Alvarez-Jimenez et al, 2013). These findings are at odds with general calls to involve patients in all stages of the design process in order to develop engaging, meaningful and clinically relevant interventions (Hagen et al, 2012).…”
Section: Methodological Issues and Future Researchmentioning
confidence: 44%
“…In fact, there is a lack of guidelines to develop such technologies for people with psychotic disorders with lower technology literacy (Rotondi et al, 2007) because, usually, self-reported technology skills are higher than demonstrated in task analyses. There are also a few implications for making these tools' usage more reasonable and acceptable for people with severe mental illness, such as having no costs, giving simple instructions to navigate, adequate font size, specific buttons and links, etc.…”
mentioning
confidence: 99%
“…Entre a literatura encontrada, pouco tem sido relatado sobre a praticidade que as pĂĄginas Web devem ter -sĂŁo exemplos raros os de autores como Sevilla et al, (2007); Rotondi et al (2007) -e nesse parĂąmetro hĂĄ menos ainda literatura sobre o que tem sido analisado sobre as preferĂȘncias dos usuĂĄrios com deficiĂȘncias intelectuais.…”
Section: Introductionunclassified